Microvascular reconstruction of a giant encephalocele defect in a 10-week-old infant - (:unkn) unknown (CHURCHILL LIVINGSTONE, 2004)
Microvascular reconstruction of a cranial defect in a 10-week-old infant, which is the youngest case in the literature, is reported. A latissimus dorsi free muscle flap was transferred to cover the defect and a split thickness skin graft was placed over the muscle flap. Despite the successful flap transfer in this case, microvascular reconstruction in an infant has its own risks and infants should be discussed as a separate entity apart from the other pediatric patients. (C) 2003 The British Association of Plastic Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: encephalocele; infant; free-flap; FREE-TISSUE TRANSFER; CHILDREN